Reliability Study of Lead Free Sn-3.8Ag-0.7Cu and Copper (Cu) Substrate based on the Microstructure, Physical and Mechanical Properties / Amares Singh...[et al.] - Singh, Amares; Durairaj, Rajkumar; Lee, Kong Chian; Sia, Yaw Yoong (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Solder alloys are vital in any electronic packaging industry especially in terms of its connectivity with the substrate. Mechanical properties are usually associated to prove and test the reliability of the solder and substrate. Ultimately, the customary Sn-Pb solders are known to be the ideal solders which solves the issue as mentioned. Sadly, this plumbum (Pb) contained solder alloy is harmful to the environment and human, leading to application of lead free solder alloys. Keeping that in perspective, this research investigates the mechanical properties of the lead free Sn-3.8Ag-0.7Cu (SAC) lead free solder alloy comprising the study in melting temperature, microstructure, wettability, shear strength and hardness. Melting temperature of the SAC solder alloy falls below the required soldering temperature of 250°C. Investigation shows that this solder alloy joint with the copper (Cu) substrate provides a low contact angle of 24.8°. Microstructure study of SAC meanwhile shows a well-defined structure with dendrite shaped Sn-matrix with wider eutectic range, which contributes to the mechanical strengthening effect. The shear strength of this solder alloy was also noted to be as high as 44.84MPa together with high hardness value of 14.4Hv. All these results clearly satisfies the environment concern and importantly confirming the reliability of the solder and substrate.